Kediri Karesidenan Sharia Tourism Routes Optimization using Genetic Algorithm - Hendy; Agata Iwan Candra; Abidatul Izzah (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2021)
Sharia tourism is a tour from nature, culture, or artificial tourism framed by Islamic values, which provides a sense of security and comfort. East Java, one of the thirteen provinces prepared by Indonesia to become a sharia tourism destination, has an excellent opportunity to be developed. One of them is Kediri Karesidenan. There are 154 destinations that can be explored and considered as sharia tourist destinations in Kediri Karesidenan. There has been no research that discusses sharia travel routes, as well as the need for government to develop sharia tourism in Indonesia, making this research very important to do. In planning the development of effective and efficient transportation routes, which reach sharia tourist destinations in Kediri Karesidenan, scientific and technological contributions are needed. A genetic algorithm is an alternative solution to searching and optimization problems. In this research, the genetic algorithm is used to determine the shortest route to reach sharia tourist destinations in five areas in Kediri Karesidenan, such as Kediri, Nganjuk, Blitar, Tulungagung, and Trenggalek. The conclusion is the length of the sharia tourism route in Kediri, Nganjuk, Blitar, Tulungagung, Trenggalek, respectively, are 249.32 km, 289.148 km 452.95 km, 341.68 km, 384.67 km. In addition, the authors used the K-means clustering algorithm to group sharia tourist destinations in Kediri Karesidenan, basic on four properties, namely: the city where the destination is located, the type of tourism, the price of admission, and the distance of the destination with the city center. It can be concluded that the best value of K is K=3, and in each resulting cluster, the authors apply the genetic algorithm to determine the shortest sharia tourism route.